Outbreak investigation of cholera in a rural community, Rivers State Nigeria: an interventional epidemiological study - Luke, Golden Owhonda; Anwuri Luke; Bright O. Ogbondah; Ifeoma Nwadiuto; Victor Abikor; Emmanuel Owhondah (International Journal Of Community Medicine And Public Health, 2023)
Cholera is a potentially life-threatening public health menace caused by a gram-negative rod-shaped bacterium known as Vibrio cholerae. This study was an epidemiological investigation of the cholera outbreak in Degema local government area (LGA), Rivers State, Nigeria. An interventional epidemiological study was conducted in a rural community between December 2021 to February 2022. All suspected cases were identified using the World Health Organization (WHO) case definition of acute watery diarrhoea. The standard outbreak investigation procedures (active case search, case management, water sanitation, hygiene) were implemented. The cholera outbreak observed two waves within an at-risk population of 373,071 in the affected LGA. Of the 35 line-listed suspected cases (male-20 versus female-15), the highest frequency was observed among those aged 0-5 years. The index case was reported on the 3rd of December in the 47th week of 2021 and abated by the 49th week, while the 2nd wave began in the 1st week of 2022 and abated by the 6th week. The stool samples result revealed; six positives for RDT, while four samples were positive by microscopy. All patients received home-based treatment except for two cases that were managed at the healthcare facility. The attack and case fatality rates were 0.01, and 8% respectively. The Rivers State public health emergency operation centre deployed standard epidemiological interventions for the containment of acute watery diarrhoea (cholera) aimed at reducing morbidity and mortality; however, vaccines were not part of the response. The deployment of vaccines and provision of potable water will improve response outcomes.